EAST JAVA ONLINE SHOPPING AT THE REGIONAL SECRETARIAT OF EAST JAVA PROVINCE - Satria, Ananda Rika; Prathama, Ananta (Natapraja, 2023)
Government procurement of goods and services plays an important role in implementation of national development for improving public services and economic development. To achieve that, requires the implementation of E-Government, one of E-Government implementation in procurement of goods and services is JATIM BEJO. The aim of this research is to determine the success implementation of Jawa Timur Belanja Online (JATIM BEJO) in Biro Pengadaan Barang/Jasa Sekretariat Daerah Provinsi Jawa Timur. This study uses a qualitative research method with a descriptive approach. Data collection techniques through interviews, observations, and documentation. The theory used in this research is based on the study and research of the Harvard JFK School of Government concering success factors of E-Government implementation, which consist of support, capacity, and value. The results of the study indicate that the implementation of JATIM BEJO for online procurement of goods and services under 50 million is considered successful because fullfil three success factors that is support, capacity, and value.